2018
DOI: 10.1038/s41386-018-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

At-risk individuals display altered brain activity following stress

Abstract: Stress is a major risk factor for almost all psychiatric disorders, however, the underlying neurobiological mechanisms remain largely elusive. In healthy individuals, a successful stress response involves an adequate neuronal adaptation to a changing environment. This adaptive response may be dysfunctional in vulnerable individuals, potentially contributing to the development of psychopathology. In the current study, we investigated brain responses to emotional stimuli following stress in healthy controls and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 47 publications
1
31
0
3
Order By: Relevance
“…In further support of such functional interactions, we found that GR agonist administration into the PrL after object recognition training induces activity-dependent neuronal activity changes within the aIC and dHPC during the postlearning consolidation period as well as structural changes in spine morphology assessed 24 h later. Our finding that GR agonist-induced enhancement of recognition memory is associated with reduced c-Fos expression, and possibly neuronal activity, of the aIC is in agreement with previous findings indicating reduced aIC neuronal activity after systemic corticosterone treatment following inhibitory avoidance training in rats (55) or after stress-induced glucocorticoid release in human subjects (56). Such reduced aIC activity might be needed to facilitate local consolidation processes, possibly by temporarily increasing the threshold for the detection of salient stimuli (23,57).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In further support of such functional interactions, we found that GR agonist administration into the PrL after object recognition training induces activity-dependent neuronal activity changes within the aIC and dHPC during the postlearning consolidation period as well as structural changes in spine morphology assessed 24 h later. Our finding that GR agonist-induced enhancement of recognition memory is associated with reduced c-Fos expression, and possibly neuronal activity, of the aIC is in agreement with previous findings indicating reduced aIC neuronal activity after systemic corticosterone treatment following inhibitory avoidance training in rats (55) or after stress-induced glucocorticoid release in human subjects (56). Such reduced aIC activity might be needed to facilitate local consolidation processes, possibly by temporarily increasing the threshold for the detection of salient stimuli (23,57).…”
Section: Discussionsupporting
confidence: 92%
“…Such reduced aIC activity might be needed to facilitate local consolidation processes, possibly by temporarily increasing the threshold for the detection of salient stimuli (23,57). Alternatively, as the aIC might work as a "switch" between different neural network systems (58), reduced aIC activity could reflect a reallocation of neural resources and therefore disinhibition of other brain systems involved in the storage of object information and higher-order cognitive processes (56). By contrast, the GR agonist administration increased the number of c-Fos-positive pyramidal cells within CA1, without affecting c-Fos expression within the dDG region of the dHPC.…”
Section: Discussionmentioning
confidence: 99%
“…2 Moreover, acute social stress deactivates the DMN in the aftermath of stress during emotion processing in healthy controls but not in siblings of schizophrenia patients who are at-risk for several psychiatric disorders. 8,9 Yet, the molecular mechanisms underlying differences in brain reactivity to stress in humans remain unknown as access to the tissue of interest in humans is limited.…”
Section: Significance Statementmentioning
confidence: 99%
“…2 Moreover, acute social stress deactivates the DMN in the aftermath of stress during emotion processing in healthy controls but not in siblings of schizophrenia patients who are at-risk for several psychiatric disorders. 8,9 Yet, the molecular mechanisms underlying differences in brain reactivity to stress in humans remain unknown as access to the tissue of interest in humans is limited.Nevertheless, stress-related brain regions and networks as identified by fMRI can be further characterized based on transcriptomic signatures. Mapping gene expression atlases of the healthy brain to imaging data allows the identification of the molecular mechanisms underlying imaging phenotypes.…”
mentioning
confidence: 99%
“…12,16 Impairments in the neural circuits that mediate the acute adaptive response may contribute to reduced access to adaptive coping, such that cognitive functions, including sustained attention and regulatory control, become compromised. 16,17 A growing number of functional imaging studies reported abnormal emotional reactivity and emotion regulation in cannabis users, including abnormal neural reactivity to affective stimuli 18,19 and deficient amygdala downregulation during cognitive reappraisal. 20 However, despite accumulating evidence for altered emotional reactivity and cognitive emotion regulation, it remains unknown whether deficient stress regulation may contribute to cannabis dependence.…”
Section: Introductionmentioning
confidence: 99%